COMMODIFICATION AND DESACRALIZATION OF RELIGIOUS SYMBOLS IN INDONESIAN HORROR MOVIES - Dhama Suroyya (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2022)
Film is a product of pop culture that consumed by society, this is because films have the ability like mass media that able to reach all aspects of people's lives. One of the film genres, is horror films, it has space in people’s or audience’s live. The public's interest in watching horror films can be seen from the sold out of ticket sales from horror films such as Perempuan Tanah Jahanan, Servant of Satan 1 & 2, Queen of Black Magic and Qodrat. The presence of religious figures becomes very important in horror films like sole authority symbolizing goodness in fighting mystical forces that are destructive and negative. The purpose of this research is to analyze the commodification and desacralization of religious figures in horror films by using a qualitative approach with the type of library research. The results of the study show that there are indications of the commodification of religious symbols in horror films and the desacralization of religious symbols in horror films produced after the New Order.